(untitled) (Comunicação & Inovação, 2022)
The work deals with the construction and communication of the brands Aliança para Inovação - articulação UFRGS, PUCRS, Unisinos, in structuring actions of Ecosystem of Inovation, and Pacto Alegre - first delivery of the Aliança when locating in Porto Alegre, next to Town Hall, movement of engagement by Quadruple Helix - mobilizing social actors - Universities, Private Initiative, Government, Civil Society. Place Branding via Case Study addresses both brands, positions them as opportunities to mobilize the community, in view of their respective identities, aiming at developing an environment of international innovation, reaching a significant level of media repercussion.